Ptolemy's Riddle III

Geometry Level 2

A cyclic quadrilateral A B C D ABCD is constructed within a circle such that A B = 3 , B C = 6 , AB = 3, BC = 6, and A C D \triangle ACD is equilateral, as shown to the right.

If E E is the intersection point of both diagonals of A B C D ABCD , what is the length of E D , ED, the blue line segment in the diagram?


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

According to Inscribed Angles Theorem , D A C = D B C = 6 0 \angle DAC = \angle DBC = 60^\circ and A B D = A C D = 6 0 \angle ABD = \angle ACD = 60^\circ because the each angle of the equilateral triangle is 6 0 60^\circ .

Therefore, the diagonal B D BD bisects A B C \angle ABC . Then suppose A B = a AB = a , B C = b BC= b , B D = d BD = d , A E = m AE = m , E C = n EC = n , and A C = c = m + n AC = c = m+n so according to Angle Bisector Theorem , a : b = m : n a:b = m:n .

In other words, a n = b m a\cdot n = b\cdot m .

Multiplying both sides by b a b-a , we will get: a n ( b a ) = b m ( b a ) a\cdot n(b-a) = b\cdot m(b-a) .

Hence, a 2 n + b 2 m = a b ( m + n ) a^{2}n + b^{2}m = ab(m+n) .

According to Ptolemy's Theorem , a c + b c = c d ac + bc = cd . Thus, d = a + b d = a+b , or B D = A B + B C BD = AB + BC .

Now considering A B C \triangle ABC , according to Stewart's Theorem , we can apply the variables, where B E = x BE = x as followed:

a 2 n + b 2 m = ( m + n ) ( x 2 + m n ) a^{2}n + b^{2}m = (m+n)(x^2 + mn)

According to Two Secants Theorem , m n = x ( d x ) = x ( a + b x ) mn = x(d-x) = x(a+b-x) .

Hence, a 2 n + b 2 m = ( m + n ) x ( x + ( a + b x ) ) = x ( m + n ) ( a + b ) a^{2}n + b^{2}m = (m+n)x(x + (a+b-x)) = x(m+n)(a+b) .

Plugging in the first finding in the earlier equation: a 2 n + b 2 m = a b ( m + n ) = x ( m + n ) ( a + b ) a^{2}n + b^{2}m = ab(m+n) = x(m+n)(a+b)

Thus, x = a b a + b x = \dfrac{ab}{a+b} , or more specifically, 1 x = a + b a b = 1 a + 1 b \dfrac{1}{x} = \dfrac{a+b}{ab} = \dfrac{1}{a}+\dfrac{1}{b} .

Now substituting a = 3 a=3 & b = 6 b=6 , we will get:

1 x = 1 3 + 1 6 = 1 2 \dfrac{1}{x} = \dfrac{1}{3}+\dfrac{1}{6} = \dfrac{1}{2} . Thus, x = B E = 2 x = BE = 2 .

Finally, E D = 3 + 6 2 = 7 ED = 3+6-2 = \boxed{7} .

The "combined theorems solution" was nice, I liked it a lot !

Sathvik Acharya - 4 years, 1 month ago

Log in to reply

Thanks! Glad to know you liked it. ;)

Worranat Pakornrat - 4 years, 1 month ago

Complicate

Auguste Richards - 4 years ago
Kevin Tong
May 14, 2017

Since quadrilateral ABCD is cyclic, A B C = ( 180 A D C ) = ( 180 60 ) = 12 0 \angle ABC = (180 - \angle ADC)^\circ = (180 - 60)^\circ = 120^\circ . Also, A B D = A C D A B D = C B D = 6 0 \angle ABD = \angle ACD \implies \angle ABD = \angle CBD = 60^\circ . Using the Law of Cosines , we see that A C 2 = A B 2 + B C 2 ( 2 A B B C cos ( A B C ) ) A C 2 = 3 2 + 6 2 ( 2 3 6 cos ( 12 0 ) ) A C 2 = 9 + 36 ( 36 1 2 ) A C 2 = 45 + 18 = 63 A C = 63 = 3 7 AC^2 = AB^2 + BC^2 - (2 \cdot AB \cdot BC \cdot \cos(\angle ABC)) \\ AC^2 = 3^2 + 6^2 - (2 \cdot 3 \cdot 6 \cdot \cos(120^\circ)) \\ AC^2 = 9 + 36 - (36 \cdot -\frac{1}{2}) \\ AC^2 = 45+18 = 63 \\ AC = \sqrt{63} = 3 \cdot \sqrt{7} To find the length of E D ED , we can use the Power of points Theorem , which, in our case, states that B E E D = A E E C BE \cdot ED = AE \cdot EC . First, let's find A E E C AE \cdot EC . Seeing that B D BD bisects A B C \angle ABC , by the Angle Bisector Theorem, we know that A E = 3 9 A C = 1 3 3 7 = 7 AE = \frac{3}{9} \cdot AC = \frac{1}{3} \cdot 3 \cdot \sqrt{7} = \sqrt{7} and E C = 6 9 A C = 2 3 3 7 = 2 7 EC = \frac{6}{9} \cdot AC = \frac{2}{3} \cdot 3 \cdot \sqrt{7} = 2 \cdot \sqrt{7} Therefore, A E E C = 7 2 7 = 7 2 = 14 AE \cdot EC = \sqrt{7} \cdot 2 \cdot \sqrt{7} = 7 \cdot 2 = 14\\

Now, to find the length of BE, we can use the Law of Cosines to get A B 2 = B C 2 + A C 2 ( 2 A C B C cos ( A C B ) ) A B 2 B C 2 A C 2 = ( 2 A C B C cos ( A C B ) ) 3 2 6 2 63 2 3 7 6 = cos ( A C B ) cos ( A C B ) = 90 36 7 = 5 2 7 AB^2 = BC^2 + AC^2 - (2 \cdot AC \cdot BC \cdot \cos(\angle ACB)) \\ AB^2 - BC^2 - AC^2 = -(2 \cdot AC \cdot BC \cdot \cos(\angle ACB)) \\ \frac{3^2 - 6^2 - 63}{-2 \cdot 3 \cdot \sqrt{7} \cdot 6} = \cos(\angle ACB) \\ \cos(\angle ACB) = \frac{-90}{-36 \cdot \sqrt{7}} = \frac{5}{2 \cdot \sqrt{7}} Using this information, we can use the Law of Cosines again to find B E BE B E 2 = B C 2 + E C 2 ( 2 B C E C cos ( A C B ) ) B E 2 = 6 2 + 4 7 ( 2 6 2 7 5 2 7 ) B E 2 = 36 + 28 ( 60 ) B E = 4 = 2 BE^2 = BC^2 + EC^2 - (2 \cdot BC \cdot EC \cdot \cos(\angle ACB)) \\ BE^2 = 6^2 + 4 \cdot 7 - (2 \cdot 6 \cdot 2 \cdot \sqrt{7} \cdot \frac{5}{2 \cdot \sqrt{7}}) \\ BE^2 = 36 +28 - (60) \\ BE = \sqrt{4} = 2 Plugging these into the original equation from the Powers of Points, we get 2 E D = 14 E D = 14 2 = 7 2 \cdot ED = 14 \\ ED = \frac{14}{2} = \boxed{7}

B y P t o l e m y s T h e o r e m B D A C = 3 C D + 6 A D , B D = 9. A C = C D = A D . U s i n g C o s R u l e i n Δ A B C , w i t h C B A = 180 A D C o f c y c l i c A B C D = 120 , A C = 3 7 . s b y D C , C B D = C A D = 60. E B A = 120 60 = 60 , a n d B E a n a n g l e b i s e c t o r . B E = B A B C ( 1 A C 2 ( A B + B C ) 2 ) = 3 6 ( 1 63 ( 3 + 6 ) 2 ) = 2. E D = B D B E = 9 2 = 7. By~ Ptolemy's ~Theorem~BD*AC=3*CD+6*AD,~\implies~BD=9.~~~\because~AC=CD=AD.\\ Using ~Cos~Rule~ in~\Delta~ABC, ~with~\angle~CBA=180-\angle~ADC~of~cyclic~ABCD=120,\\ \therefore~AC=3\sqrt7.\\ \angle s~by ~DC,~~\angle~CBD=\angle~CAD=60.~~\implies~EBA=120-60=60, ~and~ BE~an~angle ~bisector.\\ \therefore~BE=\sqrt{BA*BC \Big (1-~\dfrac{AC^2} {(AB+BC)^2} \Big )} =\sqrt{3*6 \Big (1-\dfrac{63}{(3+6)^2}\Big )}~=~2.\\ ED=BD-BE=9-2=\large~~~\color{#D61F06}{7}.

Plz correct that / CBD =/ CAD in fourth line. Thanks for this solution

Aman Bhandare - 4 years ago

After you have shown BD = 9 and AC = AD = 3√7, you can also proceed by:

∆ADE is similar to ∆BDA (equiangular), since ∠ADB is common and ∠EAD = ∠ABD = 60°

Hence ED / 3√7 = 3√7 / 9, giving ED = 7

David Faulkner - 4 years ago

Log in to reply

Thanks for alternate path.

Niranjan Khanderia - 3 years, 11 months ago
Anirban Karan
May 10, 2017

A E D \triangle AED and B E C \triangle BEC are similar triangles as A D B = A C B \angle ADB=\angle ACB and A E D = B E C \angle AED=\angle BEC .

So, E D E C = A D B C E C = E D B C A D \displaystyle\frac{ED}{EC}=\frac{AD}{BC}\implies EC=ED \cdot\frac{BC}{AD}

Again, A B E \triangle ABE and D C E \triangle DCE are also similar triangles.

So, E D E A = C D A B E A = E D A B C D \displaystyle\frac{ED}{EA}=\frac{CD}{AB}\implies EA=ED \cdot\frac{AB}{CD}

A C = E A + E C = E D [ B C A D + A B C D ] \displaystyle \implies AC= EA+EC=ED\Big[\frac{BC}{AD}+\frac{AB}{CD}\Big]

Now, A C = A D = C D AC=AD=CD as A C D \triangle ACD is equilateral.

A C = E D A C ( B C + A B ) E D = A C 2 B C + A B \displaystyle \implies AC=\frac{ED}{AC}(BC+AB) \implies ED=\frac{AC^2}{BC+AB}

But A B = 3 , B C = 6 , A B C = 18 0 A D C = 12 0 AB=3,\, BC=6,\, \angle ABC=180^\circ-\angle ADC=120^\circ

A C 2 = 3 2 + 6 2 2 × 3 × 6 cos 12 0 = 9 + 36 + 18 = 63 \implies AC^2=3^2+6^2-2\times 3\times 6 \cos 120^\circ=9+36+18=63

So, E D = 63 6 + 3 = 7 ED=\displaystyle\frac{63}{6+3}=\boxed{7}

Good method! Better than having to use Ptolemy's Theorem. You only used similarity and cosine law!

EZ Money - 4 years ago

By Ptolemy's Theorem, B D × A C = 3 × C D + 6 × A D B D = 9 BD \times AC=3 \times CD+ 6 \times AD \implies BD=9 .

A B D = A C D = D A C = D B C = 6 0 \angle ABD = \angle ACD = \angle DAC = \angle DBC = 60^{\circ} .

By cosine rule, A D 2 = 3 2 + 9 2 2 × 3 × 9 × cos ( 6 0 ) A D = 3 7 AD^2=3^2+9^2-2 \times 3 \times 9 \times \cos(60^{\circ}) \implies AD= 3 \sqrt7 .

a r ( Δ A B C ) = 1 2 × 3 × 6 × sin ( 120 ) = 9 × 3 2 ar(\Delta ABC)=\dfrac 1 2 \times 3 \times 6 \times \sin(120) = 9 \times \dfrac{\sqrt3}{2} and a r ( Δ D B C ) = 63 × 3 4 ar(\Delta DBC)= 63 \times \dfrac{\sqrt3}{4} .

a r ( Δ D A C ) a r ( Δ A B C ) = D E E B = 7 2 \dfrac{ar(\Delta DAC)}{ar(\Delta ABC)}=\dfrac{DE}{EB}=\dfrac 7 2 and D E + E B = 9 DE+EB=9 .

So, E D = 7 ED=7 .

Yes, much similar to mine. Why don't you come online at Slack ?

By theorem ,

A B C + A D C = 180 \angle ABC + \angle ADC=180

A B C + 60 = 180 \angle ABC + 60=180

A B C = 120 \angle ABC =120

Apply cosine law at A B C \triangle ABC :

A C 2 = 3 2 + 6 2 2 ( 3 ) ( 6 ) ( cos 120 ) AC^2 =3^2+6^2-2(3)(6)(\cos~120)

A C 2 = 9 + 36 36 ( 0.5 ) AC^2 =9+36-36(-0.5)

A C 2 = 63 AC^2=63

A C = 63 AC=\sqrt{63}

A C = 3 7 AC=3\sqrt{7}

By ptolemys theorem

3 ( 3 7 ) + 6 ( 3 7 ) = 3 7 B D 3(3\sqrt{7})+6(3\sqrt{7})=3\sqrt{7}BD

B D = 9 BD=9

By intersecting chords theorem

( B E ) ( D E ) = ( A E ) ( C E ) (BE)(DE)=(AE)(CE)

However, C E = 3 7 A E CE=3\sqrt{7}-AE and D E = 9 B E DE=9-BE .

Substitute

( 9 B E ) ( B E ) = ( 3 7 A E ) ( A E ) (9-BE)(BE)=(3\sqrt{7}-AE)(AE)

9 B E B E 2 = 3 7 A E A E 2 9BE-BE^2=3\sqrt{7}AE-AE^2 ( 1 ) \color{#D61F06}(1)

Apply cosine law at A B C \triangle ABC :

6 2 = 3 2 + ( 3 7 ) 2 2 ( 3 ) ( 3 7 ) ( c o s θ ) 6^2=3^2+(3\sqrt{7})^2-2(3)(3\sqrt{7})(cos~\theta)

cos θ = 2 7 \cos \theta=\dfrac{2}{\sqrt{7}}

Apply cosine law at A B E \triangle ABE :

B E 2 = 3 2 + A E 2 2 ( 3 ) ( A E ) ( 2 7 ) BE^2=3^2+AE^2-2(3)(AE)(\dfrac{2}{\sqrt{7}})

B E 2 = 9 + A E 2 12 7 A E 7 BE^2=9+AE^2-\dfrac{12\sqrt{7}AE}{7} ( 2 ) \color{#D61F06}(2)

Adding ( 1 ) \color{#D61F06}(1) and ( 2 ) \color{#D61F06}(2) , we obtain

B E = 7 A E 7 + 1 BE=\dfrac{\sqrt{7}AE}{7}+1 ( 3 ) \color{#D61F06}(3)

Substituting ( 3 ) \color{#D61F06}(3) in ( 2 ) \color{#D61F06}(2) , we obtain

6 7 A E 2 2 7 A E + 8 = 0 \dfrac{6}{7}AE^2-2\sqrt{7}AE+8=0 ( 4 ) \color{#D61F06}(4)

Using the quadratic formula in ( 4 ) \color{#D61F06}(4) , we obtain

A E = 7 AE=\sqrt{7}

Substituting 7 \sqrt{7} for A E AE in ( 3 ) \color{#D61F06}(3) , we get

B E = 2 BE=2

Finally,

E D = 9 2 = ED=9-2= 7 \color{#3D99F6}\large\boxed{7}

Thad Beier
May 17, 2017

Built a spreadsheet with two parameters -- the radius of the circle and the angle for B. A, C, and D are well defined from the radius. Modified the radius and the angle numbers until the distance from A to B was 3 and the distance from B to C was 6. Took just a couple of minutes. Then the ratio of the difference between the y component of (A - D) / (B - D) times the length of (B - D) is the answer. 7.

You have found that (A-D)/(B-D) is equal to 7 for specific parameters, how do you know that this expression can't have an alternative value?

Pi Han Goh - 4 years ago
Noor Alam
Feb 7, 2021

Jack D'Aurizio
Dec 23, 2020

By Ptolemy's theorem B E + E D = 9 BE+ED=9 and by the intersecting chords theorem B E E D = A E E C BE\cdot ED=AE\cdot EC . By the cosine theorem A C = 63 AC=\sqrt{63} and by the bisector theorem A E = 1 3 63 , E C = 2 3 63 AE=\frac{1}{3}\sqrt{63},EC=\frac{2}{3}\sqrt{63} . It follows that B E , E D BE,ED fulfill B E + E D = 9 , B E E D = 2 9 63 = 14 BE+ED=9, BE\cdot ED=\frac{2}{9}63=14 , so B E = 2 BE=2 and E D = 7 ED=7 .

Let A E = t \overline{AE}=t and A B = B C = A C = s AB=BC=AC=s . Observe that A E D \triangle AED similiar with B E C \triangle BEC . Then A E B E = A D B C B E = A E × B C A D = t s 3 \frac{AE}{BE} = \frac{AD}{BC} \Longleftrightarrow BE = \frac{AE\times BC}{AD} = \frac{ts}{3} Observe that A B E \triangle ABE similiar with D C E DCE . Then A B B E = C D C E s t s / 3 = 6 s t \frac{AB}{BE} = \frac{CD}{CE} \Longleftrightarrow \frac{s}{ts/3}= \frac{6}{s-t} We have s = 3 t s=3t , C E = 2 t CE=2t , and B E = t 2 BE=t^2 . Because A B E ABE similiar with D C E DCE , we have A B A E = A C D E D E = C E × A E B E = 2 t × t t 2 = 2 \frac{AB}{AE} = \frac{AC}{DE} \Longleftrightarrow DE = \frac{CE \times AE}{BE} = \frac{2t \times t}{t^2}= 2 We will prove that B D = A D + D C BD = AD+DC . From Ptolemy's Theorem, A B × C D + A D × B C = A C × B D A D + C D = B D AB \times CD + AD \times BC = AC \times BD \Longleftrightarrow AD+CD=BD Then B D = 3 + 6 = 9 BD = 3+6=9 . Therefore, B E = 9 2 = 7 BE=9-2=\boxed{7}

By Van Schooten's Theorem, BD = 3 + 6 = 9

By Angle Bisector Theorem, AE : EC = 1 : 2

By Inscribed Angles Theorem, Angle ABC = 120 degrees

By Law of Cosines, AC = 3 sqrt 7

By Stewart's Theorem, BE = 2

Therefore, DE = 9 - 2 = 7.

Thank you po!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...